PENGARUH SELF EFFICACY DAN SERVANT LEADERSHIP TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI JOB CRAFTING PADA KARYAWAN PDAM KOTA SURABAYA - Baskoro, Rayhan Amri Putra; Rozaq, Khoirur (Universitas Negeri Surabaya, 2024)
This research aims to examine and analyze the influence of self-efficacy and servant leadership on organizational citizenship behavior through job crafting among employees of PDAM Kota Surabaya. The study adopts a quantitative research approach, and the sampling technique employed is proportionate random sampling, with a sample size of 136 respondents. Statistical analysis in this research utilizes Structural Equation Modeling (SEM) with AMOS 24 software. The findings confirm that self-efficacy has a positive and significant effect on organizational citizenship behavior, while servant leadership also has a positive and not significant impact on organizational citizenship behavior. Additionally, self-efficacy has a positive and significant influence on job crafting, and servant leadership similarly affects job crafting positively and significantly. Job crafting, in turn, has a positive and significant impact on organizational citizenship behavior. Furthermore, job crafting mediates the influence of both self-efficacy and servant leadership on organizational citizenship behavior.